The Value of the TB IgG/IgM Rapid Test and Erythrocyte Sedimentation Rate in Relation to Xpert MTB/RIF Tests in the Diagnosis of Pulmonary Tuberculosis - Sari, Endah Permata; Lutpiatina, Leka; Insana, Aima (Tropical Health and Medical Research, 2026)
Tuberculosis (TB) remains a global health problem, requiring healthcare workers to have accurate and effective diagnostic methods. The Xpert MTB/RIF-based Molecular Rapid Test is recommended as the standard for TB diagnosis, but in clinical practice, healthcare workers still frequently use the TB IgG/IgM Rapid Test and the Erythrocyte Sedimentation Rate (ESR) as complementary tests. This study aimed to determine the relationship between Xpert MTB/RIF test results and the TB IgG/IgM Rapid Test and ESR in pulmonary tuberculosis patients at Pertamina Hospital, Balikpapan. This study used a retrospective, observational analytical study design utilizing secondary data from laboratory tests from January–December 2024. Researchers analyzed data from 250 patients who met the inclusion criteria. They analyzed the relationship between variables using the Spearman correlation test. The results showed that 16.4% of patients had MTB detected on the Xpert MTB/RIF test. Statistical analysis showed a significant positive correlation between Xpert MTB/RIF results and the TB IgG/IgM Rapid Test, with a moderate correlation strength (r = 0.562; p < 0.001). Furthermore, the analysis also showed a significant correlation between Xpert MTB/RIF results and ESR (r = 0.183; p = 0.004), but with a very weak correlation strength. The majority of patients with MTB detected by Xpert MTB/RIF had positive TB IgG/IgM Rapid Test results and abnormal ESR values. This study shows that the TB IgG/IgM Rapid Test and ESR are associated with Xpert MTB/RIF results. However, both tests have limited specificity and can therefore only be used as supporting tests and cannot replace molecular testing in the diagnosis of pulmonary tuberculosis.